DETERMINATION OF GEOTHERMAL POTENTIAL IN YANKARI GAME RESERVE, BAUCHI STATE, NIGERIA - Abubakar, I. A.; Kure, Nicodemus; Daniel, H. I.; Afuwai, C. G.; Auwal, N. (FUDMA JOURNAL OF SCIENCES, 2023)
The study deals with the determination of geothermal potential of Yankari Game reserve which involves; estimate of the Curie point depth, heat flow and geothermal gradient from spectral analysis of aeromagnetic data covering an area located approximately at longitude 9.7567 oN and Latitude 10.5094 oE. Radially power spectrum was applied to the aeromagnetic data of the study area divided into 4 square blocks and each block analyzed using the spectral centroid method to obtain depth to the top, centroid and bottom of magnetic sources. The depth values were subsequently used to evaluate the Curie-point depth (CPD), geothermal gradient and near-surface heat flow in the study area. The values of the curie point depths (Zb), range from 8.91 km to 10.11 km, with a mean value of 9.71 km, geothermal gradient, range from 57.37 oCkm-1 to 65.10 oCkm-1, with mean value of 60.10 oCkm-1 and heat flow (q), range from 143.43 mWm-2 to 162.75 mWm-2, with a mean value of 150.24 mWm-2. These results entails that the area under study has good geothermal potential for exploration.